Pemberian Tepung Singkong yang Ditambahkan Isoamilase dalam Pakan terhadap Performa Ayam Broiler: Cassava Meal Feeding with Isoamilase Addition in Rations on Broiler Perform - Mardiah Rahmadani; W Hermana; Nahrowi Nahrowi (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
Cassava has the potential use to replace corn as an energy source in poultry feed. However, the level of substitution is not optimal because of the difference ratio of amylose and amylopectin in maize and cassava. This study aimed to examine the effect of cassava flour with addition of isoamylase as a corn substitute in the ration on the performance of broilers. The material used in this study was 150 male day-old chicken broiler which were randomly divided into 3 treatments and 5 replications. The treatments were P0: 50% corn in the ration (control); P1: Substitution of 50% of corn by cassava flour; P2: Substitution of 50% of corn by cassava flour which contained 0.14% isoamylase. The variables measured were feed intake, body weight, weight gain, feed conversion ratio, income over feed and chick cost and mortality rate. Data from the complete randomized design were analyzed using Analysis of Variance, the significant results between the treatments were obtained by Duncan Multiple Range Test. The results showed that the substitution of corn by cassava flour without and with 0.14% isoamylase was not significantly affect final body weight, body weight gain, feed intake and feed conversion ratio. The most profitable Income over feed cost obtained was the treatment of P2 that is Rp 6,543.50. It can be concluded that the corn substitution by cassava flour without and with addition of 0.14% isoamylase was able to produce the same performance as broiler chickens fed with corn in the ration for five weeks of the study. Key words: broiler, isoamylase, cassava flour, performance